Histophysiological Considerations Deals Damaging of Rat’s Kidney by Examined Doses of Heroin - Abdul-Samad Uleiwi Hassan1 , Shatha Atta Abeed2 , Ashwaq Kadhem Obeid3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Scientific gain after treating about 100lab rats with heroin of several doses to examine the quantitativephysical, clinical chemistry and histopathological tests. Accompanied bymodern statistical analysis, theresults explain an obvious differentiation (p<0.05) for urine creatinine, serum creatinine, creatinine clearance,24-hour proteinuria, protein/creatinine ratio and urea; at the same time as other parameters showed slight andconcealed splendour achievements results recorded ups or downs reported below for Weight, food intake,water intake and urine volume.Judgment based on reasoning were proving the negative effects of heroin on the kidneys of the lab ratssuccesses an acute damages on the histopathological levels.